2012
DOI: 10.1111/j.1365-3148.2012.01190.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial contamination of blood products at the Croatian Institute of Transfusion Medicine: results of eleven‐year monitoring

Abstract: The results obtained in the study did not differ significantly from literature data. A number of measures to reduce the risk of bacterial contamination of blood products have been implemented at CITM. The introduction of universal screening of platelet concentrates for the presence of bacterial contamination should be taken into consideration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 17 publications
0
8
0
2
Order By: Relevance
“…Over years, CITM has implemented an array of measures to reduce the risk of bacterial contamination. Of these, mention should be made of modified disinfection of the prick site (in 1999); disposal of the initial amount of donated blood by the use of pre-donation sampling (mid 2004); BC method of blood component preparation (significantly from 2003 and fully implemented since 2005); and universal leukodepletion of PCs since 2005 (Vuk et al, 2012). Universal screening of PCs for bacterial contamination is not legally obliged in the Republic of Croatia.…”
Section: Discussionmentioning
confidence: 99%
“…Over years, CITM has implemented an array of measures to reduce the risk of bacterial contamination. Of these, mention should be made of modified disinfection of the prick site (in 1999); disposal of the initial amount of donated blood by the use of pre-donation sampling (mid 2004); BC method of blood component preparation (significantly from 2003 and fully implemented since 2005); and universal leukodepletion of PCs since 2005 (Vuk et al, 2012). Universal screening of PCs for bacterial contamination is not legally obliged in the Republic of Croatia.…”
Section: Discussionmentioning
confidence: 99%
“…We also appropriately increased residual risk of platelet bacterial contamination to account for large differences in safety measures between the two countries. The reporting of high rates of detection of bacterial contamination in all three labile components in similar settings, as described by studies performed in Germany and Croatia [19][20][21], does not reconcile easily with very low rates of adverse events in hemovigilance data [22]. By varying, simultaneously, the probability of contamination in plasma products and death due to sepsis, we showed that a specific joint probability of death from sepsis may lead to disparate ICERs in our model.…”
Section: Discussionmentioning
confidence: 89%
“…However, the relatively high incidence of contamination comparable with that found in platelet concentrates was quite surprising. Results of a recent study demonstrated a correlation between RCC contamination and frequency of poor weld in the manufacturing process (Vuk et al , ).…”
Section: Discussionmentioning
confidence: 98%